Prediction of Pop-plots at Different Temperatures - Partom, Yehuda (European Journal of Applied Sciences, 2023)
In Fig. 3 of [1], Gustavsen et al. show Pop-plots of an insensitive high explosive at six initial temperatures from -196 to 250 OC. For this range of temperature (450 OC) the run distance (or reaction rate) changes by a factor of 40. We use here our TDRR (reactant temperature dependent) reactive flow model to predict those Pop-plots. The reaction rate of TDRR increases with the temperature of the reactant, which gives it a good chance to succeed in predicting the experimental results. And indeed, our predictions of the six Pop-plots shown by Gustavsen, are all within the experimental error brackets.